Use of Role Playing With Video Recording to Develop Interviewing Skills in Students of Psychology - Suárez-Cretton, Ximena (2020)
The research is a teaching innovation experience through a simulation strategy, role play, little used in university teaching. The purpose was to verify if role play with video recording is an effective strategy for acquiring interviewing skills, and explore if it helps the development of meaningful learning in students. The method considered a mixed type investigation and a pre-experimental design of a single measurement at the end. The pedagogical intervention was conducted in the Work Psychology course for four months. The main strategy used was role-playing. Thirteen students participated; they were enrolled in this course. After the intervention, to estimate the impact of the experience, an evaluation was made through three instruments: a meaningful learning scale from Guirao-Goris et al. (2007), a questionnaire of didactic innovation from Bartlett y Morrow (2001), and a rubric to evaluate the achievement of the skill. Data were descriptively analyzed. The results show a favorable assessment from the students towards the strategy used to achieve effective learning, perception from the students of significant learning achievement, and an evaluation from the professor endorsing the achievement of learning the interviewing skill.